Emerging Security Technologies and EU Governance Actors, Practices and Processes - Calcara, Antonio; Csernatoni, Raluca; Lavallée, Chantal (Routledge Studies in Conflict, Security and Technology, 2020)
"This book examines the European governance of emerging security technologies. The emergence of technologies such as drones, autonomous robotics, artificial intelligence, cyber and biotechnologies has stimulated worldwide debates on their use, risks, and benefits in both the civilian and the security-related fields. This volume examines the concept of 'governance' as an analytical framework and tool to investigate how new and emerging security technologies are governed in practice within the European Union (EU), emphasizing the relational configurations among different state and non-state actors. With reference to European governance, it addresses the complex interplay of power relations, interests, and framings surrounding the development of policies and strategies for the use of new security technologies. The work examines varied conceptual tools to shed light on the way diverse technologies are embedded in EU policy frameworks. Each contribution identifies actors involved in the governance of a specific technology sector, their multi-level institutional and corporate configurations, and the conflicting forces, values, ethical, and legal concerns, as well as security imperatives and economic interests. This book will be of much interest to students of science and technology studies, security studies and EU policy."